Teknologi IoT dalam Peningkatan Kenyamanan dan Efisiensi Ruang Kelas di MTs Miftahussalam - Rahmad, Iwan Fitrianto; Aditya, Elsa; Rahmad, Sofyan; Siregar, Rahmadani; Harahap, Nur Anzelina; Ardani, Tira (Publikasi Pengabdian Masyarakat, 2025)
The Internet of Things (IoT) technology plays a significant role in enhancing environmental efficiency and comfort, including in supporting teaching and learning activities. This community service program aimed to design and implement an IoT-based automatic control system for lights and fans in the classrooms of MTs Miftahussalam. The system was developed using an ESP8266 microcontroller, DHT11 temperature and humidity sensor, and relay modules to control devices automatically based on environmental data. Monitoring and control interfaces were handled via the Arduino IoT Cloud platform, allowing real-time device management through web or mobile applications. The implementation results showed that the system operated stably and effectively, providing positive impacts on classroom comfort and energy efficiency. This activity also successfully improved teachers' technological literacy through hands-on training and practical system assembly.